2011 South Florida Beef Forage Survey Results - Sonja Crawford; Christa Kirby; Tycee Prevatt; Brent Sellers; Maria Silveira; Bridget Stice; Joao Vendramini; Lindsey Wiggins (EDIS)
UF/IFAS Extension faculty and state specialists involved in the UF/IFAS South Florida Beef-Forage Program (SFBFP), in conjunction with the UF/IFAS Program Evaluation and Organizational Development unit, created a survey in 1982 that is used to evaluate ranch management practices. The survey is updated and distributed every five years to ranchers in 14 south Florida counties. Written by Sonja Crawford, Christa Kirby, Tycee Prevatt, Brent Sellers, Maria Silveira, Bridget Stice, Joao Vendramini, and Lindsey Wiggins, and published by the UF/IFAS Agronomy Department.